Analysis of Dominant Factors that Effect Delayed Diagnosis in Women with Breast Cancer in Baladhika Husada Hospital Jember (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Delayed diagnosis will have an impact on poor prognosis and complicate the treatment of breast cancer, contributing to low life expectancy for breast cancer patients. The study aims to find the factors that play the most role in influencing the behavior of women with breast cancer as well as dig deeper into the things behind the patient in making decisions that have an impact on delayed diagnosis. Methods: The study uses an analytical observational design with quantitative and qualitative mixed methods. Collecting data was conducted from April until June 2021 on 76 women with breast cancer at Baladhika Husada Hospital Jember based on classification into case and control groups. The sampling method used purposive sampling and the Lemeshow formula. Results: The results showed the factor that dominates the occurrence of delayed diagnosis is alternative medicine (p = 0.013; OR 11.03). Based on the results of the study, patients who undergo alternative medicine are 11 times more at risk of delayed diagnosis of breast cancer compared to patients who do not undergo alternative treatment.Conclusions: The patient’s background in choosing alternative medicine is supported by various reasons including concerns about medical treatment methods, concerns about nominal medical costs, and negative information from the surrounding. Thus, it can be concluded that the dominant factor affecting the delay in the diagnosis of women with breast cancer is alternative medicine.